Holographic polymer dispersed liquid crystal material, grating device and preparation method thereof

By introducing alicyclic epoxy acrylate and unsaturated monomers with different functionalities into the holographic polymer dispersed liquid crystal material, the degradation problem of the material in high temperature environment is solved, and the heat-resistant aging performance of the material and the grating device are improved. Service life.

CN118894972BActive Publication Date: 2025-02-18NIKA OPTICS (TIANJIN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411388107.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-18
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Holographic polymer dispersed liquid crystal materials are prone to degradation of polymer matrix in high temperature environments, resulting in insufficient heat aging resistance of the material, affecting the performance and service life of the grating device.

Method used

By introducing alicyclic epoxy acrylate into the holographic polymer dispersed liquid crystal material and selecting unsaturated monomer combinations with different functionalities, an unsaturated monomer system is formed, which improves the polymerization degree and cross-linking rigidity, thereby enhancing the material's resistance Thermal aging performance.

Benefits of technology

It improves the thermal stability of holographic polymer dispersed liquid crystal materials, extends the service life of grating devices, and reduces production costs, and is suitable for a wider range of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof, wherein the holographic polymer dispersed liquid crystal material comprises alicyclic epoxy acrylate and other unsaturated monomers, wherein the first monomer is selected from 4-tert-butyl cyclohexyl acrylate, cyclohexyl methacrylate, and dicyclopentyl methacrylate; the second monomer is selected from tricyclodecane dimethanol dimethacrylate, ethoxylated 1,6-hexanediol diacrylate, and dipropylene glycol diacrylate; the third monomer is dipentaerythritol hexaacrylate or di-trimethylolpropane tetraacrylate. The present invention improves the polymerization degree and crosslinking rigidity between unsaturated monomers in the holographic polymer dispersed liquid crystal material through the crosslinking synergistic effect between the alicyclic epoxy acrylate and the unsaturated monomers, thereby improving the heat aging resistance of the material, and making the holographic volume grating device prepared by the holographic polymer dispersed liquid crystal material have better comprehensive performance and service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of holographic projection display, and more specifically, to a holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof. Background Art

[0002] Liquid crystal is one of the fastest-growing, most widely used and most closely related optoelectronic materials since the last century. It is still widely used in the display of various electronic devices. Thanks to the tunable properties of liquid crystal materials, the arrangement direction of liquid crystal molecules can be controlled by applying external fields such as electric fields, magnetic fields, and heat, thereby realizing different functions of the device, greatly improving the multi-dimensional flexible controllability of devices in the current electronics industry. Among them, polymer dispersed liquid crystal (PDLC) is an optoelectronic functional device based on liquid crystal / polymer materials. It mainly transforms the mixture of liquid crystal and prepolymer into liquid crystal droplets dispersed in the polymer substrate by photopolymerization or thermal polymerization to cause phase separation. Then, the electrical control characteristics of liquid crystal are used to control the orientation of liquid crystal molecules by applying an external voltage, thereby changing the refractive index of liquid crystal to match or mismatch the refractive index of polymer, resulting in the polymer dispersed liquid crystal film switching between light transmission or light scattering under the action of an electric field.

[0003] Holographic Polymer Dispersed Liquid Crystal (H-PDLC) is a combination of holographic technology and polymer dispersed liquid crystal. It is a composite material with holographic display function and a certain ordered arrangement structure system. H-PDLC is formed by periodic arrangement of polymer-rich phase and liquid crystal-rich phase. It is formed by polymerization-induced phase separation under coherent laser. Specifically, a laser beam is divided into two coherent beams of equal light intensity, and then converged to obtain an interference light field with a sinusoidal distribution of light intensity, and light intensity modulation is generated in the interference area; in the interference bright fringe area (i.e., coherent bright area), the photoinitiator system absorbs light energy, generates active free radicals, and initiates monomer polymerization. The polymerization reaction causes the chemical potential of the system to change, causing the monomer to diffuse from the coherent dark area to the coherent bright area, and the liquid crystal diffuses to the coherent dark area, and finally produces a holographic grating structure composed of alternating polymer-rich phases and liquid crystal-rich phases. Holographic polymer dispersed liquid crystal materials have a variety of functions and have been widely used in electro-optical response photonic crystals, color 3D holographic image storage, distributed feedback lasers, sensors and other fields. In addition, due to its excellent electro-optical response characteristics and high refractive index modulation, holographic polymer dispersed liquid crystal materials also show great application potential in the field of augmented reality.

[0004] As a composite material, holographic polymer dispersed liquid crystal materials usually cause problems such as polymer matrix degradation under high temperature environment. The reason is that when thermally degradable polymers are exposed to high temperature for a long time, the movement of polymer chains will intensify. Once the dissociation energy of chemical bonds is exceeded, thermal degradation of polymer chains will occur. The thermal degradation of polymers can be roughly divided into three categories: depolymerization, random chain scission, and side group removal. Among them, depolymerization and random chain scission are to break polymers into monomers and low molecular weight substances, so that the degree of polymerization is reduced. Side group removal may remove side groups while keeping the degree of polymerization basically unchanged, so that the molecular weight of polymers is slightly reduced. The heat aging resistance of grating devices prepared by holographic polymer dispersed liquid crystal materials mainly depends on the polymer materials in the polymer-rich area. Under long-term high temperature conditions, the polymers in the polymer-rich area will undergo thermal degradation, and the molecular chains will break into small molecules or groups will fall off, so that the small liquid crystal molecules in the liquid crystal area will flow into the cracks of the polymer, resulting in an increase in the overall refractive index of the polymer area and shortening the refractive index difference with the liquid crystal area. Therefore, in order for the holographic polymer dispersed liquid crystal material to maintain stable performance for a long time, it is necessary to improve the thermal stability of the material. Specifically, it is mainly necessary to increase the heat aging resistance of the high molecular weight polymer in the polymer region. Summary of the invention

[0005] The present invention aims to overcome at least one defect of the above-mentioned prior art and provides a holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof, thereby improving the thermal stability of the holographic polymer dispersed liquid crystal material, thereby improving the comprehensive performance and service life of the holographic polymer dispersed liquid crystal material and the grating device prepared therefrom.

[0006] The technical solution adopted by the present invention is first to provide a holographic polymer dispersed liquid crystal material, which comprises, by mass percentage:

[0007] Solvent: 5%-15%,

[0008] LCD: 35-55%,

[0009] Photoinitiator: 0.5-2%,

[0010] Co-initiator: 0.5-10%,

[0011] Alicyclic epoxy acrylate: 5-20%

[0012] First monomer: 0-40%,

[0013] Second monomer: 0-40%,

[0014] The third monomer: 0-10%;

[0015] The first monomer is selected from one or more of 4-tert-butyl cyclohexyl acrylate, cyclohexyl methacrylate, and dicyclopentyl methacrylate;

[0016] The second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated 1,6-hexanediol diacrylate, and dipropylene glycol diacrylate;

[0017] The third monomer is one or more of di-trimethylolpropane tetraacrylate and dipentaerythritol hexaacrylate.

[0018] Alicyclic epoxy acrylate is a type of compound obtained by reacting alicyclic epoxy resin with acrylic acid. It inherits the advantages of alicyclic epoxy resin, such as good processability, high heat resistance, small curing shrinkage, good electrical properties, UV resistance and good weather resistance. In the present technical scheme, alicyclic epoxy acrylate is introduced into the holographic polymer dispersed liquid crystal material. At the same time, an unsaturated monomer system is formed by selecting a first monomer, a second monomer and a third monomer with different functionalities. The cross-linking synergistic effect between alicyclic epoxy acrylate and unsaturated monomers improves the polymerization degree and cross-linking rigidity between unsaturated monomers in the holographic polymer dispersed liquid crystal material, thereby improving the heat aging resistance of the material. Specifically, by adjusting the type and proportion of the added alicyclic epoxy acrylate and the added unsaturated monomer, the efficiency of the polymerization reaction between monomers in the material can be adjusted, and at the same time, the diffraction efficiency and heat resistance stability of the prepared holographic grating device can be specifically adjusted and improved. Specifically, the first monomer is a monofunctional monomer selected from one or more of 4-tert-butylcyclohexyl acrylate, cyclohexyl methacrylate, and dicyclopentyl methacrylate; the second monomer is a bifunctional monomer selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated 1,6-hexanediol diacrylate, and dipropylene glycol diacrylate; the third monomer is a monomer having six functional groups, dipentaerythritol hexaacrylate or di-trimethylolpropane tetraacrylate. In the present technical scheme, the thermal stability of the holographic polymer dispersed liquid crystal material is improved by the combined use of alicyclic epoxy acrylate and unsaturated monomers, so that the holographic volume grating device prepared by the holographic polymer dispersed liquid crystal material has better comprehensive performance and service life. At the same time, the unsaturated monomers contained in the holographic polymer dispersed liquid crystal material can be selected and combined from polymer monomers with different functionalities, and the selection is diverse, and the source of raw materials is wide and easy to obtain. While ensuring the function of the holographic volume grating device, it improves the production convenience and reduces the production cost.

[0019] Furthermore, the photoinitiator is selected from one or more of Rose Bengal, Rhodamine B, and Ethyl Eosin.

[0020] Furthermore, the co-initiator is selected from one or more of N,N-dimethylaniline and N-phenylglycine.

[0021] Furthermore, the liquid crystal is selected from one or more of E7, E63, and BL038.

[0022] Furthermore, the solvent is selected from one or more of dimethylallylamine, dimethylformamide, and N-ethylpyrrolidone.

[0023] Another object of the present invention is to provide a method for preparing a holographic polymer dispersed liquid crystal grating device. The preparation method has a simple process, does not require post-curing, has low production cost, and high production efficiency. The preparation method specifically comprises the following steps:

[0024] The holographic polymer dispersed liquid crystal material provided in the technical solution is mixed and poured into a liquid crystal box, placed still in a dark room, and then interference exposed under the interference light field of a double-beam light source.

[0025] Optionally, the interference exposure time is 1-5 min, and the irradiation power is 4-6 mW / cm 2 ; The angle between the dual-beam light sources is 30°-60°.

[0026] Preferably, a double beam angle of 45° and an optical power of 5 mW / cm 2 The material was exposed to a dual-beam light source for 3 min to prepare a holographic polymer dispersed liquid crystal grating device.

[0027] Optionally, the thickness of the liquid crystal box is 5 μm-10 μm.

[0028] Preferably, the holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.

[0029] Another object of the present invention is to provide a holographic polymer dispersed liquid crystal grating device, which is prepared by the preparation method provided by the technical solution.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: by introducing alicyclic epoxy acrylate into the holographic polymer dispersed liquid crystal material, and selecting a first monomer, a second monomer and a third monomer with different functionalities to form an unsaturated monomer system, the polymerization degree and crosslinking rigidity between the unsaturated monomers in the holographic polymer dispersed liquid crystal material are improved through the crosslinking synergistic effect between the alicyclic epoxy acrylate and the unsaturated monomers, thereby improving the heat aging resistance of the material.

[0031] Secondly, the thermal stability of the holographic polymer dispersed liquid crystal material is improved by adjusting the combination type and ratio between the alicyclic epoxy acrylate and the unsaturated monomer, so that the holographic volume grating device prepared by the holographic polymer dispersed liquid crystal material has better comprehensive performance and service life. At the same time, the unsaturated monomers contained in the holographic polymer dispersed liquid crystal material can be selected and combined from polymer monomers with different functionalities, and the selection is diverse, and the source of raw materials is wide and easy to obtain. While ensuring the function of the holographic volume grating device, it improves the production convenience and reduces the production cost. DETAILED DESCRIPTION

[0032] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0034] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or according to the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels).

[0035] Since the high-temperature aging performance of holographic polymer dispersed liquid crystal materials mainly depends on the aging performance of the high-molecular polymer in the polymer zone, in the present technical scheme, the component composition and proportion setting of the polymer monomers in the holographic polymer dispersed liquid crystal materials are adjusted to increase the cross-linking degree and structural rigidity of the polymer, so as to increase the heat aging resistance of the polymer zone in the material, thereby improving the overall aging performance of the volume holographic material.

[0036] In the technical scheme, the polymer monomer includes alicyclic epoxy acrylate and a first monomer, a second monomer and a third monomer with different functionalities. Among them, the alicyclic epoxy acrylate is prepared by reacting with acrylic acid on the basis of alicyclic epoxy resin. Epoxy resin refers to a class of organic polymer compounds containing two or more epoxy groups in the molecule, and the molecular chain contains active epoxy groups; the epoxy ring of the alicyclic epoxy resin is located on the alicyclic ring, and is synthesized by peroxidizing the double bonds in the alicyclic olefins, so it has the characteristics of good processability, high heat resistance, small curing shrinkage, good electrical properties, UV resistance and good weather resistance. Alicyclic epoxy acrylate not only inherits the advantages of alicyclic epoxy resin, but also introduces double bonds in the compound by reacting with acrylic acid, which facilitates the participation of alicyclic epoxy acrylate in the photocuring reaction in the holographic polymer dispersed liquid crystal material.

[0037] Furthermore, on the basis of introducing alicyclic epoxy acrylate, an unsaturated monomer system is formed by selecting a first monomer, a second monomer and a third monomer with different functionalities. By adjusting the type and proportion of the added unsaturated monomer, the efficiency of the polymerization reaction between the monomers in the material is adjusted, thereby promoting the cross-linking synergistic effect between the alicyclic epoxy acrylate and the unsaturated monomer.

[0038] Example 1

[0039] This embodiment provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0040] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:

[0041] Rose Bengal 1.5%, N-phenylglycine 5%, E7 35%, cyclohexyl methacrylate 15%, tricyclodecane dimethanol dimethacrylate 17%, alicyclic epoxy acrylate 15%, di-trimethylolpropane tetraacrylate 4%, dimethylformamide 3%, N-ethylpyrrolidone 4.5%.

[0042] (2) Preparation of holographic polymer dispersed liquid crystal materials

[0043] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0044] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0045] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0046] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0047] (4) Diffraction efficiency test and haze test

[0048] The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.

[0049] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.

[0050] (5) Aging test

[0051] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Heat Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged for 200 hours in 80°C hot air. The above material is subjected to an aging test, and the diffraction efficiency and haze after aging are tested.

[0052] Example 2

[0053] This embodiment provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0054] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:

[0055] Rhodamine B 1%, N, N-dimethylaniline 3.5%, BL038 38%, cyclohexyl methacrylate 5%, alicyclic epoxy acrylate 19%, dipropylene glycol diacrylate 15%, dipentaerythritol hexaacrylate 3%, ethoxylated 1,6-hexanediol diacrylate 10%, dimethylformamide 5.5%.

[0056] (2) Preparation of holographic polymer dispersed liquid crystal materials

[0057] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0058] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0059] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0060] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0061] (4) Diffraction efficiency test and haze test

[0062] The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.

[0063] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.

[0064] (5) Aging test

[0065] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Heat Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged for 200 hours in 80°C hot air. The above material is subjected to an aging test, and the diffraction efficiency and haze after aging are tested.

[0066] Example 3

[0067] This embodiment provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0068] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:

[0069] Ethyl eosin 1%, N,N-dimethylaniline 6%, E63 38%, 4-tert-butylcyclohexyl acrylate 10%, alicyclic epoxy acrylate 18%, tricyclodecane dimethanol dimethacrylate 16%, dipentaerythritol hexaacrylate 3%, dimethylallylamine 3%, N-ethylpyrrolidone 5%.

[0070] (2) Preparation of holographic polymer dispersed liquid crystal materials

[0071] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0072] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0073] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0074] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0075] (4) Diffraction efficiency test and haze test

[0076] The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.

[0077] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.

[0078] (5) Aging test

[0079] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Heat Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged for 200 hours in 80°C hot air. The above material is subjected to an aging test, and the diffraction efficiency and haze after aging are tested.

[0080] Example 4

[0081] This embodiment provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0082] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:

[0083] Rose Red 1.5%, N, N-dimethylaniline 3%, E63 34%, dicyclopentane methacrylate 8%, dipropylene glycol diacrylate 14%, alicyclic epoxy acrylate 12%, ethoxylated 1,6-hexanediol diacrylate 20%, dipentaerythritol hexaacrylate 7%, dimethylallylamine 3%, dimethylformamide 4.5%.

[0084] (2) Preparation of holographic polymer dispersed liquid crystal materials

[0085] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0086] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0087] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0088] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0089] (4) Diffraction efficiency test and haze test

[0090] The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.

[0091] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.

[0092] (5) Aging test

[0093] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Heat Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged for 200 hours in 80°C hot air. The above material is subjected to an aging test, and the diffraction efficiency and haze after aging are tested.

[0094] Comparative Example 1

[0095] This comparative example provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0096] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:

[0097] Rose Bengal 1%, N-phenylglycine 3.5%, E7 38%, 4-tert-butylcyclohexyl acrylate 11.5%, dicyclopentyl methacrylate 16%, tricyclodecane dimethanol dimethacrylate 18%, di-trimethylolpropane tetraacrylate 4%, N-ethylpyrrolidone 8%.

[0098] (2) Preparation of holographic polymer dispersed liquid crystal materials

[0099] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0100] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0101] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0102] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0103] (4) Diffraction efficiency test and haze test

[0104] The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.

[0105] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.

[0106] (5) Aging test

[0107] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Heat Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged for 200 hours in 80°C hot air. The above material is subjected to an aging test, and the diffraction efficiency and haze after aging are tested.

[0108] Comparative Example 2

[0109] This comparative example provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0110] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:

[0111] Rhodamine B 1%, N-phenylglycine 3%, BL038 35%, 2-phenoxyethyl methacrylate 29%, ethylene glycol dimethacrylate 17%, ethoxylated 1,6-hexanediol diacrylate 8%, dipentaerythritol hexaacrylate 3%, dimethylformamide 4%.

[0112] (2) Preparation of holographic polymer dispersed liquid crystal materials

[0113] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0114] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0115] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0116] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0117] (4) Diffraction efficiency test and haze test

[0118] The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.

[0119] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.

[0120] (5) Aging test

[0121] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Heat Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged for 200 hours in 80°C hot air. The above material is subjected to an aging test, and the diffraction efficiency and haze after aging are tested.

[0122] Comparative Example 3

[0123] This comparative example provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0124] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:

[0125] Ethyl eosin 1%, N,N-dimethylaniline 6%, E63 38%, 4-tert-butylcyclohexyl acrylate 20%, tricyclodecane dimethanol dimethacrylate 21%, dipentaerythritol hexaacrylate 6%, dimethylallylamine 3%, N-ethylpyrrolidone 5%.

[0126] (2) Preparation of holographic polymer dispersed liquid crystal materials

[0127] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0128] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0129] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0130] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0131] (4) Diffraction efficiency test and haze test

[0132] The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.

[0133] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.

[0134] (5) Aging test

[0135] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Heat Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged for 200 hours in 80°C hot air. The above material is subjected to an aging test, and the diffraction efficiency and haze after aging are tested.

[0136] In Examples 1 to 4, the holographic polymer dispersed liquid crystal material is selected and combined from the components and formulas provided in the technical solution. When alicyclic epoxy acrylate is added, a first monomer, a second monomer and a third monomer with different functionalities are selected to form an unsaturated monomer system. Specifically, the first monomer is selected from one or more of 4-tert-butylcyclohexyl acrylate, cyclohexyl methacrylate, and dicyclopentyl methacrylate; the second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated 1,6-hexanediol diacrylate, and dipropylene glycol diacrylate; and the third monomer is dipentaerythritol hexaacrylate. By introducing alicyclic epoxy acrylate into the holographic polymer dispersed liquid crystal material and the crosslinking synergistic effect between the unsaturated monomers, the polymerization degree and crosslinking rigidity between the unsaturated monomers in the holographic polymer dispersed liquid crystal material are improved, thereby improving the heat aging resistance of the material.

[0137] In the holographic polymer dispersed liquid crystal materials provided in Comparative Examples 1 and 3, the selected polymer monomers are selected from the first monomer, the second monomer and the third monomer provided in the technical solution, but do not include the alicyclic epoxy acrylate provided in the technical solution. In the holographic polymer dispersed liquid crystal material provided in Comparative Example 2, at least one type of polymer monomer among the selected first monomer, the second monomer or the third monomer is selected from other monomers that are not within the selection range of the first monomer, the second monomer and the third monomer provided in the technical solution.

[0138] The results of the diffraction efficiency change rates of the seven holographic polymer dispersed liquid crystal materials and the grating devices prepared therefrom in Examples 1 to 4 and Comparative Examples 1 to 3 after aging tests are shown in the following table:

[0139]

[0140] By comparing the embodiments and the comparative examples, it can be found that the obtained diffraction efficiency change rate results after the aging test show that when the alicyclic epoxy acrylate and the unsaturated monomer contained in the holographic polymer dispersed liquid crystal material are selected and combined according to the polymer monomer range provided in the present invention, the absolute value of the diffraction efficiency change rate of the prepared holographic polymer dispersed liquid crystal grating device after a long-term aging test is greatly reduced, indicating that the holographic polymer dispersed liquid crystal material obtained in the embodiment and the grating device prepared therefrom have a smaller change amount of the device under a longer high-temperature aging condition, and its comprehensive performance is more stable, that is, it has better thermal stability, so that the prepared holographic polymer dispersed liquid crystal grating device has better comprehensive performance and longer service life, and is also suitable for a wider range of usage scenarios.

[0141] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A holographic polymer dispersed liquid crystal material, characterized in that: In terms of mass percentage, it includes: Solvent: 5%-15%, LCD: 35-55%, Photoinitiator: 0.5-2%, Co-initiator: 0.5-10%, Alicyclic epoxy acrylate: 5-20% First monomer: 0-40%, Second monomer: 0-40%, The third monomer: 0-10%; The first monomer is selected from one or more of 4-tert-butyl cyclohexyl acrylate, cyclohexyl methacrylate, and dicyclopentyl methacrylate; The second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated 1,6-hexanediol diacrylate, and dipropylene glycol diacrylate; The third monomer is one or more of di(trimethylolpropane) tetraacrylate and dipentaerythritol hexaacrylate; The mass percentages of the first monomer, the second monomer, and the third monomer are not 0; The photoinitiator is selected from one or more of Rose Bengal, Rhodamine B, and Ethyl Eosin; The co-initiator is selected from one or more of N,N-dimethylaniline and N-phenylglycine.

2. The holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The liquid crystal is selected from one or more of E7, E63, and BL038.

3. The holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The solvent is selected from one or more of dimethylallylamine, dimethylformamide, and N-ethylpyrrolidone.

4. A method for preparing a holographic polymer dispersed liquid crystal grating device, characterized in that: The following steps are involved: The holographic polymer dispersed liquid crystal material according to any one of claims 1 to 3 is mixed and poured into a liquid crystal box, placed still in a dark room, and then subjected to interference exposure under the interference light field of a double-beam light source.

5. The preparation method according to claim 4, characterized in that: The interference exposure time is 1-5 min, the irradiation power is 4-6 mW / cm2; and the angle between the dual-beam light sources is 30°-60°.

6. The preparation method according to claim 4, characterized in that: The thickness of the liquid crystal cell is 5-10 μm.

7. The preparation method according to claim 4, characterized in that: The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum atmosphere and left to stand in a dark room for 1 hour.

8. A holographic polymer dispersed liquid crystal grating device, characterized in that: Prepared by the preparation method according to any one of claims 4 to 7.

Citation Information

Patent Citations

  • Polymer dispersed liquid crystal holographic volume grating and preparation method thereof

    CN115141636A